Amr Binā' Ma'nā Al-Amr Wa Al-Nahī: Dirāsah Nahwiyyah Taba'ātih Al-Fiqhiyyah - Hasbullah; Noor, Muhammad Syamsuddin (UIN ANTASARI, 2025)
The study of amr (command) and nahy (prohibition) occupies a significant position in both Arabic linguistics and Islamic legal theory (uṣūl al-fiqh). Traditionally, these two concepts have often been examined separately: grammar (naḥw) emphasizes structural forms, while uṣūl al-fiqh focuses on normative implications. This separation has created a methodological gap in interpreting Islamic law. The present study aims to integrate these perspectives in order to achieve a more comprehensive understanding. This research employs a qualitative method through a library research approach. Primary sources include classical works of grammar such as Ibn Hishām’s Mughnī al-Labīb and works of uṣūl al-fiqh such as al-Ghazālī’s al-Mustaṣfā and al-Shāṭibī’s al-Muwāfaqāt. The analysis identifies the grammatical forms of amr and nahy and then explores their legal implications within the framework of uṣūl principles. The findings indicate that amr, in grammatical terms, is characterized by the imperative verb (fiʿl al-amr), while nahy is marked by the prohibitive particle lā al-nāhiyah attached to the present tense verb (fiʿl al-muḍāriʿ). In uṣūl al-fiqh, the default meaning of amr is obligation (wujūb), and nahy is prohibition (taḥrīm). However, these meanings may shift to recommendation (sunnah), permissibility (ibāḥah), or reprehensibility (karāhah) if supported by strong contextual or textual evidence (qarīnah). These results highlight the importance of integrating grammar and uṣūl al-fiqh to ensure the precision of legal derivation.